A review on analytical methods for the Estimation of dapagliflozin in bulk and its Formulations - M. Sunitha; P. Venkatesh; D. Vamshi; D. Vamshi; H. Pavan Kumar; M. Narendra; Chennupati Suresh; KV. Ramanjineyulu (International Journal of Pharmacy and Analytical Research, 2025)
This review focuses on the analytical methods developed for the estimation of Dapagliflozin in bulk and pharmaceutical formulations. Introduction, drug profile, structure, mechanism of action, pharmacokinetics and also Techniques like UV-spectroscopy, HPLC, TLC, LC-MS, FTIR, GC have been extensively utilized for its qualitative and quantitative analysis. The study highlights the importance of method validation parameters, including accuracy, precision, linearity, and sensitivity by some authors like key parameters by (author name) A comprehensive overview of the drug’s analytical profile is provided, with supporting tables, graphs, and references to guide researchers and analysts in drug quality assessment.